Penafsiran Ekstensif Kerugian Keuangan Negara Dalam Korupsi Sumber Daya Alam Sektor Timah: Studi Komparatif Negara-Negara Berkembang - Daffa Ladro Kusworo; Titi Anggraini (Integritas: Jurnal Antikorupsi, 2024)
The precedent of state losses in regulations is still limited to the paradigm of nominal losses, which is clearly different from the type of corruption in natural resources, particularly when considering environmental damage benchmarks in ecological, economic, and environmental recovery aspects. Unfortunately, Article 2, Paragraph 1, and Article 3 of the Eradication of Criminal Acts of Corruption Law, which defines the term “state financial losses,” creates confusion in interpretation because it is different from other regulations, such as Minister of Environment Regulation No. 7/2014. In this regulation, state economic losses due to environmental damage and recovery costs are included as non-tax state revenue. It's unfortunate that government's right to sue in civil realm is used for compensation, and not for environmental restoration. This practice creates a conflict between corruption losses in the environmental aspect and the paradigm of state finances. This research is based on a doctrinal method that refers to legislation as the basis for hypothesis testing to dichotomize the interpretation of state losses, accompanied by a comparison with other countries. The results show that state financial losses interpretation needs to be seen casuistically through multi-regime investigation paradigm, namely by combining formulation unlawful acts between regulations. In fact, the practice of natural resource corruption is rampant in developing countries due to a lack of determination regarding losses and appropriate environmental corruption sanctions for perpetrators.